IMMEDIATE AND DELAYED HYPERSENSITIVITY REACTIONS TO PROTON PUMP INHIBITORS: A REVIEW ARTICLE - Ćorović, Vahida; Ćorović, Irfan; Ademović, Vahid; Gegić, Altan; Dazdarević Zećirović, Mirzeta; Ćorović, Kemal; Suljić, Lejla; Ćorović Ličina, Emina; Ziljkić, Vahid; Plojović, Haris; Maksić, Mladen; Džanković, Fuad; et al. (Sanamed, 2025)
Proton pump inhibitors (PPIs) are among the most widely prescribed medications in clinical practice, primarily used for managing acid-related gastrointestinal disorders. While generally regarded as safe, with adverse effects being rare and typically mild, PPIs have been associated with hypersensitivity reactions. These reactions, which may be immediate or delayed, vary in severity from mild to potentially life-threatening. This review provides an in-depth analysis of key aspects of PPI use, with a particular emphasis on the pathophysiological and clinical characteristics of both immediate and delayed hypersensitivity reactions. It also explores cross-reactivity among PPIs and offers a practical framework to assist clinicians in diagnosing and managing these conditions effectively. Additionally, the review highlights the critical need for further research to develop standardized diagnostic and therapeutic protocols, enabling personalized and evidence-based care for patients experiencing PPI-related hypersensitivity.